Persiapan menghadapi puberitas bagi remaja awal di SD Pertiwi Makassar - Eva Meizara Puspita Dewi; Resekiani MasBakar (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
One of characteristics of puberty in teenage girls ismenarche (or first menstruation). This is not a simple stage. Itrequires psychological understanding and preparation indealing with it through providing psychoeducation. Thispsychoeducation activity was designed systematically andmeasurably to produce a module on puberty education in earlyadolescents which was equipped with a test of participants'understanding on puberty and menstruation before and afterjoining the psychoeducation. The number of participants whoparticipated in this activity was 75 students. The methods usedare lectures, discussions, audiovisuals and games. The resultsshowed that the post-test score proved to be greater than thepre-test score. It can be concluded that the treatment in theform of psychoeducation namely knowledge of puberty andreadiness for menarche can increase adolescents' readiness infacing menarche.